Production of Briquette Made of Sugarcase Bagasse and Dry Leaves Mixture by Microwave Torrefaction Using Tapioca Flour as Adhesive - Gina Ayuningtiyas; Faris Harditya; Erlinda Ningsih (Future Science)
The purpose of the research was to identify the effect of time and microwave torrefaction power to heat value, water content, and ash content to recognize the maximum condition of the selected variables. Biomass waste and garbage can be one energy resource alternatives. The real exploitation of biomass resulted from forestry and estate activity waste that has been widely adopted is found in the production of briquette and charcoal. We adopted sugarcane bagasse and dry leaves mixture was to generate greater contents of cellulose and lignin to get higher heat value. One of the methods commonly adopted in briquette productions is microwave torrefaction. The process in the research covered raw material drying, slicing, microwave torrefaction, proximate analysis, data processing, and research finding discussion. The torrefaction process was activated by reacting to the raw materials, i.e.: sugarcane bagasse and dry leaves into a microwave under 230'C through 280oC in airtight condition and in a short time. The variables in the research were microwave power and torrefaction time. The microwave power was set at 80 W, 400 W, and 800 W, while the ten faction time set 5 minutes, 15 minutes, and 25 minutes. Based on the results of the research it was concluded that the most optimum variables were microwave power of 800 W and torrefaction time of 25 minutes.